Ecological and environmental predictors of juvenile coral density across the central and western Pacific - Couch, Courtney S.; Oliver, Thomas A.; Dettloff, Kyle; Huntington, Brittany; Tanaka, Kisei R.; Vargas-Ángel, Bernardo (Frontiers in Marine Science, 2023)
The persistence of Pacific coral reefs is threatened by large-scale mortality resulting from heat stress, storms, overfishing, disease, and land-based pollution. While reefs have demonstrated the ability to recover from these disturbances, recovery potential is highly variable; in part driven by the high spatial variability in the abundance of coral juveniles. However, our understanding of the patterns and predictors of juvenile coral density is hampered by the limited geographic scope of previous studies. Our objectives in this study were to: (1) explore the spatial and temporal patterns of juvenile (1- < 5cm in diameter) colony density across the U.S. affiliated Pacific islands and atolls; and (2) identify the potential role of ecological and environmental factors which may influence coral juvenile abundance. Juvenile density was quantified as part of NOAA’s National Coral Reef Monitoring Program between 2013 and 2019 using a stratified sampling design across 1,405 forereef sites on 34 islands and atolls. Regional mean juvenile density varied from 1.4 to 10.5 colonies m-2 with the highest densities observed in the northern Mariana Islands, Northwestern Hawaiian Islands, and southern Mariana Islands. Juvenile density significantly increased between sampling periods in the Main Hawaiian Islands, Line Islands and northern Mariana Islands. Survey-weighted generalized linear modeling demonstrated that juvenile density was best predicted by the interaction between time since a heat stress event and heat stress severity, depth, site and sector-level percent coral cover, human density, percent unconsolidated substrate, macroalgal cover, herbivore biomass, and the interaction of sector coral cover area and heat stress, and the interaction of wave power (combination of wave height and period) and heat stress. With the unique scale and gradients across the U.S. Pacific, our study found that the high latitude regions have enhanced juvenile density compared to their lower latitude counterparts. Our results also suggest density is dependent on stock-recruitment with an open adult population, availability of suitable habitat at the site-scale, timing and severity of heat stress, wave energy during heat stress, and the number of humans in the system.